When Governance Trembles: Resilience as Contested Terrain in Urban Tourism - Faisal, Abrar; Shoeb-Ur-Rahman, Muhammad; Hoque, Md Ariful (Informa UK Limited, 2026)
Resilience in urban tourism is often framed as a technical capacity or organisational attribute; however, this five-year longitudinal qualitative study of tourism governance in an emerging-economy urban context reconceptualises it as a contested terrain – a fragile accomplishment forged at moments when governance trembles. Drawing on semi-structured in-depth interviews with government and industry actors in Dhaka, Bangladesh, the paper demonstrates how resilience emerges not as a state of equilibrium but as a provisional and uneven outcome shaped by multi-scalar disruptions, institutional asymmetries, and politically mediated negotiations. Governance actors navigated cascading shocks by improvising, recalibrating mandates, and negotiating competing imperatives, thereby exposing the limitations of universalist and capability-driven models of resilience. The study contributes a critical, processual understanding of resilience, attentive to power, temporality, and institutional complexity in tourism crisis governance. It further demonstrates how longitudinal, interpretive inquiry illuminates evolving meanings, relational tensions, and bounded adaptive capacities through which governance actors make sense of uncertainty and sustain fragile forms of coherence.
Keywords: 1506 Tourism; 3508 Tourism; 4406 Human geography; Resilience; crisis governance; urban tourism; longitudinal study; political ecology